QTL-Seq and Fine-Mapping Analyses Identify QTL and Candidate Genes Controlling Snake-like Pod Surface Trait in Vegetable Cowpea Yardlong Bean - Khwanruedee Thepphomwong; Makawan Srichan; Artitaya Deeroum; Kularb Laosatit; Prakit Somta (Plants)
Yardlong bean is a vegetable type of cowpea grown for fresh and immature pods. “Thua Ngu” is a specialty yardlong bean cultivar with its unique snake-like pod surface and highly crispy pods that may be useful for the breeding of a new cultivar(s). The objectives of this study were to determine the mode of inheritance of the snake-like pod trait and locate the genome region controlling this trait in Thua Ngu. Microscopic observation revealed that the shape, size, and organization of cells of immature and mature pods of Thua Ngu were clearly different from those of “Raya” (normal yardlong bean). Fiber analysis showed that lignin content in immature and mature pods of Thua Ngu was 2.05- and 3.45-fold higher than that in Raya. Segregation analysis using F2 and F2:3 populations of the cross Thua Ngu × Raya demonstrated that a single gene controls the snake-like pod trait. QTL-seq analysis using the F2 population revealed a major locus, qSlp4.1, for the snake-like pod trait. Fine-mapping using F2 and F2:3 populations delimited qSlp4.1 to a 152.88 Kbp region containing nine genes. Genes with functions involved in cell morphology and/or lignin formation, including Vigun04g163400, Vigun04g163600, and Vigun04g163700, were identified as candidate genes for the snake-like pod trait.